Pre-Operative Serum Albumin As A Predictor of Abdominal Wound Related Complications in Patients Undergoing Emergency Exploratory Laparotomy - Jokhio, Sharmeen Nadeem; Zulfiqar, Imrana; Jamal, Ayesha; Sheikh, Kainat; Tahir, Sana; Khan, Bushra Saeed (Biological and Clinical Sciences Research Journal, 2025)
Hypoalbuminemia is recognized as a key indicator of poor surgical outcomes, particularly in emergency settings. In patients undergoing emergency exploratory laparotomy, preoperative serum albumin levels may serve as a predictive marker for postoperative wound-related complications such as surgical site infections (SSI) and wound dehiscence. Early identification of at-risk patients can help guide perioperative nutritional and wound management strategies. Objective: This study aims to evaluate the predictive value of preoperative serum albumin levels for postoperative wound-related complications in patients undergoing emergency exploratory laparotomy, including surgical site infections and wound dehiscence. Methods: After the ethical approval from the institutional review board, this prospective observational study was conducted at the Department of General Surgery in Dr Ruth KM PFAO Civil Hospital Karachi, from 1st October 2024 to 30th December 2024.Through non probability consecutive sampling, 100 patients aged 18-75 years, both gender, undergoing Emergency exploratory laparotomy, and whose preoperative serum albumin screen results become available within 24 hours preceding their operation Results: The comparison of serum albumin levels between patients with and without postoperative wound infections and wound dehiscence revealed significant findings. Patients with serum albumin levels below 3.5 g/dL had a higher occurrence of wound infections (12 vs. 32 patients, p = 0.107), though the association was not statistically significant. However, for wound dehiscence, the relationship with serum albumin was highly significant (p = 0.001), as 12 patients with albumin levels below 3.5 g/dL developed wound dehiscence compared to only two patients with levels above 3.5 g/dL. Additionally, the presence of comorbidities did not show a statistically significant association with postoperative wound infection (p = 0.509). Conclusion: Patients with low preoperative serum albumin levels face higher risks of developing postoperative wound problems which mainly include surgical site infections and wound dehiscence.